Transition metal-free synthesis of 3-trifluoromethyl chromones via tandem C-H trifluoromethylation and chromone annulation of enaminones - Yu, Qing; Liu, Yunyun; Wan, Jie-Ping (ORGANIC CHEMISTRY FRONTIERS, 2020)
The tandem C-H bond trifluoromethylation and chromone annulation reactions ofo-hydroxyphenyl enaminones have been realized for the practical synthesis of 3-trifluoromethyl chromones. The reactions are performed efficiently with the promotion of K(2)S(2)O(8)without using any transition metal catalyst or additive. In addition, the 3-trifluoromethyl chromone products have been successfully used for the synthesis of 3-trifluoromethyl pyrimidines by reacting with guanidine/amidine substrates.